Ecological, economic and socio-cultural sustainability of different livelihood options and enterprises practised by pastoralists in Banni grasslands of Gujarat - MANJUNATHA, B L; SHAMSUDHEEN, M; SURESHKUMAR, M; TEWARI, PRATIBHA (The Indian Journal of Animal Sciences, 2021)
The present study was conducted in Banni grasslands to estimate the sustainability of different livelihood options practiced by pastoralist households. The sustainability of livelihood options was measured using a scale consisting of ecological, economic and socio-cultural parameters with 6 indicators each. The primary data were collected from 280 households in 12 villages in Banni grasslands between 2014 and 2019. It was found that there were 11 distinct livelihood options practiced in Banni grasslands: Banni buffalo based pastoralism, goat and sheep rearing, Prosopis juliflora based charcoal production, honey collection, gum extraction, embroidery, leather work, labour, services, tourism and trade. The sustainability of buffalo rearing was found to be highest on ecological, economic and socio-cultural indicators. Migratory pastoralism has evolved over five centuries adapting to climatic and man-made changes, has deep socio-cultural heritage and employed 70% households at present while generating highest revenues to individual households and the Banni economy. The economic sustainability of charcoal production was higher than the goat and sheep rearing whereas the ecological and socio-cultural sustainability of the latter was higher. Charcoal production employed 80% households (as primary and secondary enterprise) whereas goat and sheep rearing employed merely 3% households indicating the economic significance of the former enterprise. It was evident that economic sustainability was the immediate goal of individual pastoralist households to attain income, food and nutritional security. Goat and sheep rearing could provide an alternative to charcoal production while being more sustainable. Charcoal production was an adaptation strategy for livelihood security. Control of P. juliflora will have positive implications on the ecology of Banni grasslands and livelihoods of pastoralists. The recognition of community grazing rights of Maldharis over Banni grasslands would further augment this shift. Similarly, handicrafts (embroidery and leather craft) and trade offer sustainable alternatives to charcoal production in the context of expanding tourism and market access.